AB0535 Concentrated Autologous Bone Marrow Aspirate Transplantation for Corticosteroid-Induced Osteonecrosis of the Femoral Head in Systemic Lupus Erythematosus. (9th June 2015) - Akaogi, H.; Tomaru, Y.; Yoshioka, T.; Sugaya, H.; Aoto, K.; Wada, H.; Hyodo, K.; Nakatani, T.; Ochiai, N.; Yamazaki, M.; Mishima, H.
Abstract : Background: We developed and have been using a concentrated autologous bone marrow aspirate transplantation (CABMAT) technique to treat osteonecrosis of the femoral head (ONFH) since April 2003. Objectives: The purpose of this study was to evaluate the clinical and radiographic findings of CABMAT for corticosteroid-induced ONFH in systemic lupus erythematosus (SLE). Methods: Between April 2003 and March 2009, a total of 26 SLE patients (46 hips) with corticosteroid-induced were treated with the CABMAT protocol. Among the 46 hips, 43 hips in 24 patients (8 men and 16 women; mean age, 34 years) were followed for a minimum of 5 years after the transplantation. The mean follow-up period was 79.4 months (range, 60–121 months). The diagnosis, classification, and staging of ONFH were based on the 2001 Japanese Orthopaedic Association (JOA) classification using anteroposterior and lateral plain X-rays or magnetic resonance imaging (MRI) scans. CABMAT was conducted as follows: bone marrow was aspirated from the iliac crest and concentrated using a conventional manual blood bag centrifugation technique to extract the buffy coat. The interface between the areas of ONFH was perforated with multidirectional holes made by drilling with Kirschner wires. The aspirate was then injected into the ONFH area. For the clinical evaluation, the criteria for hip joint function proposed by the Japanese Orthopaedic Association (JOA hip score) were used. The progression of the femoral head collapse was radiographically evaluated using plain X-rays and MRI. A Kaplan-Meier survival analysis was used to compare the progression to total hip arthroplasty (THA) for each hip type. Results: The mean JOA hip score was 72.5 before surgery and 84.3 at the last follow-up examination. The score had significantly improved after the CABMAT, and for 72% patients, it was over 70. The number of hips that had not collapsed or had the minimum extent of collapse (progression of collapse less than 2 mm) was as follows: 2 type A hips (100%), 2 type B hips (100%), 14 type C1 hips (77.8%), and 6 type C2 hips (28.6%). In the ONFH hips without collapse or with only a crescent sign on plain X-ray (stages 1 and 2) before surgery, 20 hips (76.9%) did not collapse or had less than 2 mm of collapse. In hips in which the femoral head had already collapsed (stages 3A, 3B), 4 hips (23.5%) did not collapse or had less than 2 mm of collapse. Ten hips (23.3%) underwent THA. In hips with a larger necrotic area of the femoral head shown on the lateral view of the MRI, the incidence of collapse was higher. Reduction of the necrotic lesion was seen in some femoral heads. The cumulative rates of survival were 100% at 5 years for both type C1and type C2 hips, 92.3% at 10 years for type C1 hips, and 24.5% at 10 years for type C2 hips. No specific complications were observed. Conclusions: The results showed that the CABMAT technique could preserve the femoral head and provided significant clinical improvement. This technique is less invasive than those of other osteotomies. We thought that the CABMAT technique could be a good treatment option for ONFH in SLE. ONFH with a relatively small necrotic area (types A-C1) and in the early stage (stages 1, 2) are good indications for CABMAT. Disclosure of Interest: None declared